Ephesos Yamaç Ev 2 : Arkeolojik Bir Rehber - LADSTÄTTER, Sabine (Ege Yayınları, 2012)
An archaeological guide to Hanghaus 2 in Ephesos. Mention of floor, wall and vault mosaics (opus tessellatum and opus sectile) decorating the residential units. Book available also in a German edition: Das Hanghaus 2 in Ephesos. Ein archäologischer Führer (voir notice n° 8370).
283 p., 239 ill. coul.
Keywords: Bibliographie par pays, région ou ensemble géographique; Mosaïque [de voûte]; Maison (Éphèse, TUR) « Hanghaus »; Opus sectile; Guide archéologique; Mosaïque [pariétale]; Placage mural; Éphèse